The Effectiveness of the Read Aloud Method assisted by the Let’s Read Digital Application on Reading Comprehension Skills - Fristayana, Lollita; Kaltsum, Honest Ummi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to describe the effectiveness of the Read Aloud method assisted by the Let's Read digital application on students' reading comprehension skills in elementary school. Methodology: This study uses Pre-Experimental research with One-Group Pretest-Posttest Design. The research instruments used were in the form of pretest and posttest questions for reading comprehension. The data analysis technique uses normality test, homogeneity test, hypothesis test, and N-Gain test with the help of SPSS Windows Release 25.0 data processing. The subject of this study is the fourth grade students of SDN Wonokerso 3 with a total of 24 students. Results: The results of the study showed an N-Gain value of 0.6125 or 61.25%. This means that the effectiveness of the Read Aloud method assisted by the Let's Read digital application on students' reading comprehension skills is quite effective by being in the medium category. Applications/Originality/Value: This study integrates the Read Aloud method and the Let's Read digital application in students' reading comprehension skills in elementary school which have not been explored in depth in previous research, thus making a new contribution to educational literature. This research can pave the way for further research that explores the potential for collaboration between learning methods and digital technology in the context of primary education.